The TSH Test in Persons Having Received Iodine Compounds - Papadopoulos, S. N.; Livadas, D.; Sfontouris, J.; MacFariane, S.; Koutras, D. A. (Nuklearmedizin - NuclearMedicine, 1968)
The 2-hr 132I thyroid uptake was measured serially in 5 groups of normal volunteers whereas the 2-hr and the 24-hr uptake of 131I were measured in a sixth group. Following administration of potassium iodide in doses of 40, 200 and 1000 mg, Urografin or Biligrafin i.v., the thyroid uptake decreased to very low values. A single injection thereafter of 10 I.U. of TSH increased these low values to levels within the normal range. A direct assessment of the individual level of thyroid function cannot be obtained by the described procedure because of lack of linear correlation between the values obtained for the PII and the uptake measurements after TSH administration. It is concluded that TSH can be used for differentiating low uptake values due to primary hypothyroidism from those after iodine ingestion in either inorganic or organic form. In such patients, TSH may also help in obtaining a better scintigram of the thyroid gland.